Orientation of the strongest velocity pulses and the maximum structural response to pulse-like ground motions. Issue 136 (September 2020) - Li, Cuihua; Zuo, Zhanxuan; Kunnath, Sashi; Chen, Linli
Abstract: The ground motion pulse-like effect depends on its orientation, it is thus necessary to identify the direction of the ground motion with the strongest pulse. A simple yet efficient method to identify the strongest pulse over all orientations in multicomponent ground motions is presented in this study, through rotating the ground motions to the orientation associated with the maximum peak ground velocity ( PGV ). It is demonstrated that the pulse-like ground motion components in the orientation with the maximum PGV value have the potential to produce the largest mean/median ductility than the components rotated to all remaining orientations. A comparison of the proposed methodology with an existing method is also performed, further demonstrating that the proposed maximum PGV methodology can accurately identify the strongest pulse. The determined strongest pulse can be utilized in engineering practice to estimate the maximum seismic demands on structures. Highlights: The maximum PGV method is proposed to identify the strongest pulses to estimate the maximum structural demands. Pulses in the maximum PGV orientation produce the largest structural displacement. Motions in the maximum PGV orientation is likely to contain the most significant pulse. Ground motion amplitude, frequency and duration parameters show polarization features. Pulse-like features tend to be polarized with the maximum PGV direction.